X-ray shielding polyurethanes: Synthesis and characterization. Issue 2 (17th February 2017) - Kiran, S.; Joseph, Roy
ABSTRACT: Synthesis and characterization of X-ray shielding thermoplastic polyurethane elastomers which are capable of blocking harmful radiation emitted by various sources are reported. X-ray shielding capability was generated in the polymer by covalently binding iodine atoms in a monomer and polymerizing it with other monomers such that the resultant polymer has the capability of shielding X-radiation. For rendering X-ray shielding capability to the polyurethane, Bisphenol-A (BPA) was iodinated to 4, 4′-isopropylidinedi-(2, 6-diiodophenol) (IBPA) and it was used as a chain extender during the synthesis of polyurethane. Polyurethanes were synthesized by reacting 1, 6-diisocyanatohexane and IBPA with two different polyols, namely, poly(tetramethylene glycol) and poly(hexamethylene carbonate) diol. X-ray shielding polyurethanes (XPU) were characterized by infrared spectroscopy, thermogravimetry, dynamic mechanical analysis, energy-dispersive X-ray analysis, gel permeation chromatography, and X-radiography. Studies showed that by effectively changing polyol from polyether to polycarbonate, XPUs having different physicomechanical properties could be manufactured. Furthermore, these polyurethanes were also found to be noncytotoxic to L929 fibroblast cell lines. X-ray images revealed that the incorporation of IBPA has rendered X-ray opacity to the polyurethanes which are several times higher than the aluminum wedge of equivalent thickness. The materials are sufficiently flexible and rubbery, so can be used as coatings, films, or sheets for applications in energy sector, power-generating nuclear power plants, defense sector (bunkers for army personnel), medical applications (X-ray diagnostic and CT scanner rooms, gamma radiation therapy of cancer), etc.